COMPUTERIZED ADMINISTRATION EDUCATION SYSTEM IN INDONESIA MANAGEMENT DEVELOPMENT INSTITUTE - Siti Wardah; Ir. Aqwam Rosadi Kardian (Jurnal Sistem Informasi, 1997)
Computerization as an alternative to meet the smoothness and timeliness in thehandling of a system of educational administration Indonesian Institute forManagement Development. With the computer that exists as data processing devices,the increased capacity of education administrative services IPMI can be realized, andto help search and control of service activities, because the computer is an effectivetools to process data in large quantities and are repeated so as to obtain efficiencyemployment, though the ability of large amounts of data and data storage isorganized.